The Effect Of Environmental, Social, And Governance (ESG) Disclosure On Company Performance (Accounting, Financial, Operational, And Market) In Energy Sector Companies In Indonesia - Ahmad Kurniawan Pranata; Katiya Nahda (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) disclosure on company performance which includes accounting, financial, operational, and market performance of energy sector companies in Indonesia. This study uses a quantitative approach with secondary data obtained from financial statements and sustainability reports of 29 energy sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. The measurement of ESG disclosure is based on the Global Reporting Initiative (GRI) indicators of the GRI 2, GRI 300, and GRI 400 standards. The company's performance is measured through Return on Assets (ROA), Return on Equity (ROE), Logarithm Natural Cost of Goods Sold (LNCOGS), and Logarithm Natural Market Capitalization (LNMKP), while the control variables used include Firm Age, Debt to Equity Ratio (DER), and Current Ratio (CR). Data analysis was carried out using the panel data regression method using Eviews 13. The results of the study show that ESG disclosure does not have a significant effect on the company's performance from accounting, financial, operational, and market aspects. These findings indicate that ESG disclosure in energy sector companies in Indonesia has not been able to make a real contribution to improving company performance during the study period.